STUNTING DETERMINANTS IN KULONPROGO DISTRICT, YOGYAKARTA YEAR 2019 - Desi Nurfita; Annisa Parisudha; Sugiarto Sugiarto (Universitas Ahmad Dahlan, 2022)
Background: UNICEF stated that in 2014, about 66% of children aged less than five years in lower-middle-income countries were stunted. Stunting is a predictor of poor quality of human resources and reduces a nation's productivity in the future. Stunting control in the Kulonprogo District is one of the priority districts in Indonesia. This study aimed to analyze the determinants of stunting in the Kulonprogo District. Methods: This research was conducted in Kuponprogo District. The population was children under five in Kulonprogo District. Analysis was done through a descriptive approach. Descriptive quantitative research was used by employing secondary data from the year 2013. Results: The prevalence of stunting among children under five in the Kulonprogo District was 11.12%, spread across all primary health centers (Puskesmas) in the Kulonprogo District. The three puskesmas with the highest prevalence rate were Puskesmas Girimulyo 2, Puskesmas Samigaluh 2, and Puskesmas Kalibawang. The analysis found that low-income families, maternal education, age at pregnancy, chronic energy deficiency during pregnancy, anemia during pregnancy, early initiation of breastfeeding, exclusive breastfeeding, and parenting mode are the determinant factors of stunting in the Kulonprogo District in 2019. Conclusion: Several determinants of stunting were found, namely low-income families, maternal education, age at pregnancy, chronic energy deficiency during pregnancy, anemia during pregnancy, early initiation of breastfeeding, exclusive breastfeeding, and parenting mode.